33rd European Symposium on Computer Aided Process Engineering : ESCAPE-33 - Kokossis, Antonis Constantinos; Georgiadis, Michael C.; Pistikopoulos, Stratos (Computer-aided chemical engineering, 2023)
33rd European Symposium on Computer Aided Process Engineering: ESCAPE-33, Volume 52 contains the papers presented at the 33rd European Symposium of Computer-Aided Process Engineering (ESCAPE) event held in Athens, Greece. It is a valuable resource for chemical engineers, chemical process engineers, researchers in industry and academia, students and consultants in the chemical industries.